Enhancing E. coli tolerance towards oxidative stress via engineering its global regulator cAMP Receptor Protein (CRP) - Basak, Souvik (2013)
Oxidative damage to microbial hosts often occurs under stressful conditions during bioprocessing. Classical strain engineering approaches are usually both time-consuming and labor intensive. Here, we aim to improve E. coli performance under oxidative stress via engineering its global regulator cAMP receptor protein (CRP), which can directly or indirectly regulate redox-sensing regulators SoxR and OxyR, and other ~400 genes in E. coli. Error-prone PCR technique was employed to introduce modifications to CRP, and three mutants (OM1~OM3) were identified with improved tolerance via H2O2 enrichment selection. The best mutant OM3 could grow in 12 mM H2O2 with the growth rate of 0.6 h−1, whereas the growth of wild type was completely inhibited at this H2O2 concentration. OM3 also elicited enhanced thermotolerance at 48°C as well as resistance against cumene hydroperoxide. The investigation about intracellular reactive oxygen species (ROS), which determines cell viability, indicated that the accumulation of ROS in OM3 was always lower than in WT with or without H2O2 treatment. Genome-wide DNA microarray analysis has shown not only CRP-regulated genes have demonstrated great transcriptional level changes (up to 8.9-fold), but also RpoS- and OxyR-regulated genes (up to 7.7-fold). qRT-PCR data and enzyme activity assay suggested that catalase (katE) could be a major antioxidant enzyme in OM3 instead of alkyl hydroperoxide reductase or superoxide dismutase. To our knowledge, this is the first work on improving E. coli oxidative stress resistance by reframing its transcription machinery through its native global regulator. The positive outcome of this approach may suggest that engineering CRP can be successfully implemented as an efficient strain engineering alternative for E. coli.